Thermoacoustic regfrigeration from waste heat - Mohd Ghazali, Normah (Universiti Teknologi Malaysia, 2006)
Thermoacoustic effect is basically the interaction of acoustic waves with solid boundaries. The discovery that the phenomena can generate cooling for refrigeration has escalated research into thermoacoustic heat engine and refrigeration systems since the late twentieth century. Thermoacoustic systems are attractive due to the overall simplicity of the devices, absence of critical dimensions with few moving parts, and environmentally friendly operations. The research under vote 71891 is to produce acoustic waves from biomass waste heat generated by the portable combustion unit (PCU) at the Combustion Laboratory of the Faculty of Mechanical Engineering, UTM. The acoustics are to be used to generate cooling for thermoacoustic refrigeration. The fundamental working concept has been understood, and the design and fabrication of the heat engine was completed. Some experiments were done to identify the respective sources of waste heat and important parameters of the thermoacoustic heat engine.